Performance and immunological resistance of Litopenaeus vannamei fed a β-1,3/1,6-glucan-supplemented diet after per os challenge with the Infectious myonecrosis virus (IMNV) - Sabry Neto, Hassan (2015)
This study determined the efficacy of a β-1,3/1,6-glucan source on the survival, growth, and immunological responses of Litopenaeus vannamei challenged with infectious myonecrosis virus (IMNV). The work was conducted in 20 tanks of 500 L with clear water with constant recirculation and aeration. Shrimp weighing 2.6±0.4 g were stocked at 100 animals/m2 and reared for 10 weeks. Viral challenge occurred through oral administration of IMNV positive extract (1.82 £ × 103 copies of IMNV/μL RNA) during three consecutive days, twice a day. One treatment and three controls, with five replicate tanks each, were used, as follows: Com - commercial diet fed to non-challenged shrimp (NCS); Ref - lab-manufactured basal diet, deprived of β-1,3/1,6-glucan fed to NCS; IMNV-Ref - basal diet fed to IMNV-challenged shrimp; and, IMNV-BetG - basal diet with 1,000 mg/kg of a β-1,3/1,6-glucan. Per os challenge began on the 29th day of rearing (4.93-g to 6.92-g shrimp). Shrimp were effectively contaminated with IMNV. Animals were highly susceptible to IMNV four weeks after the first day of infection when mortality peaked. Shrimp in the Com treatment (69.5±12.7%) reached the highest survival, but it did not differ from the Ref group (57.9±9.21%). Shrimp under the IMNV-Ref treatment achieved the lowest survival (23.2±5.76%). Survival for IMNV-BetG (48.1±8.53%) was significantly higher than IMNV-Ref, and similar to the Ref group. Total hemocyte count was significantly affected by treatment and hemolymph sampling time, while serum protein concentration and phenoloxidase activity did not change. Addition of 1,000 mg/kg of β-1,3/1,6-glucan in a diet for L. vannamei enhances shrimp survival when orally exposed to IMNV. No signs of immunological fatigue or detriment in growth are detected when the species is continually exposed to this diet.